Penerapan Pembelajaran Kooperatif Tipe Mind Mapping untuk Meningkatkan Motivasi Belajar Siswa Kelas VII-K13 Mata Pelajaran Akhlak Materi Jujur dan Bohong di SMP Annur Bululawang Malang - Nila Rosyidah; Anwar Sa’dullah; Achmad Faisol (VICRATINA, 2019)
This study aims to describe the application of cooperative learning type mind mapping to improve the learning motivation of  VII-KI3 student in honest and lying  subjects in the Annur Bululawang Malang. The actual classical problem which is a fundamental problem in education today, especially in isalamic religious education, is the still weak learning process that occurs in the classroom. In the process, students are not encouraged to develop thinking skill, thus causing low student motivaton. Rather than that, the reseacher applied cooperative learning type mind mapping to overcome it. This study use s a classroom action research method. For data acquisition, this study was obtained from action taken by teacher, observation, documentation,  interviews and some field notes as strong evidence of research. Then it is analyzed by reducing the data, then the data is explained and finally the conclusion is drawn. The results of this study indicate that the application of mind mapping type of cooperative learning succeeded in increasing student motivation and getting good feedback from student.